Integrating Flipped Classroom with Guided Inquiry Based on Digital Literacy Using Discord on Atomic Structure for First Year Chemistry Students - Feliska Amanda; Mawardi (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to develop an integrated flipped classroom learning system based on guided inquiry using the Discord platform for teaching atomic structure to first-year chemistry students. The research employed the Plomp development model. Research instruments included a validation form completed by five chemistry lecturers from UNP, an interview guide for one-on-one evaluations with three students, and a practicality questionnaire answered by nine students and two lecturers. Content and construct validity were analyzed using Aiken’s V coefficient, while practicality was evaluated through a percentage-based analysis. The findings showed that the developed product met the validity standards, achieving Aiken’s V values of 0.90 and 0.91, and demonstrated high practicality levels, with scores of 92% from students and 91% from lecturers. These results indicate that the integrated flipped classroom system incorporating guided inquiry through Discord is valid and practical for use in chemistry learning, particularly on the topic of atomic structure.